Breed predispositions to disease in dogs and cats - Gough, Alex, 1971-; Thomas, Alison, 1964-; O'Neill, Dan (Dan G.) (Wiley, 2018)
Breed Predispositions to Disease in Dogs and Cats, Third Edition provides a comprehensive exploration of current knowledge of breed predispositions based on rigorous examination of primary research. -Incorporates the latest research, new testing methods, and newly-discovered predispositions and diseases -Provides expanded information on genetics, epidemiology, and longevity -Includes key characteristics of diseases, including pathogenesis, genetics, risks, and common presentations -Indexes dogs and cats by breed, with listings of common inherited and predisposed disorders organized by body system -Includes absolute and relative frequency/occurrence data for conditions, along with references to further information.